Tinjauan Hukum Islam Terhadap Pembiayaan Pengadaan Barang (Studi Komparasi Antara Skema Murabahah Lil Wa’id Bisyira' dan al-Ijarah Ma’al Wa’di Bil Hibah) - Muhammad Shiddiq Abdillah; Muh Fadel As’ad (AL-KHIYAR: Jurnal Bidang Muamalah dan Ekonomi Islam, 2022)
This research was conducted with the following objectives: (1) to find out whether the murabahah lil wa'id bisyira and ijarah ma'al wa'di bil grant schemes can be a sharia solution for financial institutions seeking profit from the circulation of funds or not; (2) to find out the difference between the murabahah lil wa'id bisyira and ijarah ma'al wa'di bil grant schemes. This research uses a qualitative approach with library research method (library study). The results show that the murabahah lil wa'id bisyira and ijarah ma'al wa'di bil grant schemes can be a sharia solution for conventional financing that contains usury. Each scheme has its own character, thus presenting options for financing institutions to choose the most according to the needs of the financing product.